BEAM WEIGHT OPTIMIZATION IN RADIOTHERAPY TREATMENT PLANNING BY CALCULATING THE VALUE OF OVERDOSE AND UNDERDOSE USING THE SIMULATED ANNEALING METHOD - Toti Paringan, Adinda
Radiotherapy is a method of cancer treatment is still being developed to get more effective and efficient treatment results. The treatment can be carried out after going through the Radiotherapy Treatment Planning (RTP) process or the radiotherapy planning process. To get the expected results, an optimization process is performed on RTP. The process of optimization of RTP is aided by computational methods, one of which is the simulated annealing method used in this final project. The aspect reviewed in the RTP optimization process in this final project is the optimization of file weights. To get the optimal file weight results, an objective function is used which is a mathematical model that can be used to find the global optimum value of a case, both the maximum and minimum values depending on the case to be tested. The objective function used in the optimization process in planning radiotherapy takes into account the dose limits allowed for healthy organs, and also as many doses as possible for the target. The objective function used in this final assignment will be compared with the objective function used in previous research with the aim of obtaining better optimization results. Then the function will be applied to CT data of lung cancer patients to get an overview of the application of optimization in the real case.